Face recognition based on landmark and support vector machine - Afifi, Hassan; Hsaini, Abdallah Marhraoui; Merras, Mostafa; Bouazi, Aziz; Chana, Idriss (Institute of Advanced Engineering and Science, 2025)
Nowadays, the fast development of face recognition technologies used in fields such as security and video surveillance, gives us many theories and algorithms, a view of these algorithms provides us with an idea of their performance and limitations. In this paper, we will develop a new face recognition approach using the face estimation landmark algorithm to detect faces in real-time videos. Then, we use a pre-trained neural network to extract the 128 facial features of each face detected in the database images and register each vector of 128 values with the corresponding person’s name. Then, we form the linear support vector machine (SVM) classifier to recognize faces. Extensive experiments on real and generated data are presented to demonstrate the quality of the proposed method in terms of accuracy, reliability, and speed.